Answer:
(-3,-1)
Step-by-step explanation:
-x+y=2
3x-5y=-4
in the top equation, we can get y by itself on one side of the equation:
-x+y=2
y=x+2
now, since we know that y=x+2, in the bottom equation we can substitute x+2 for y (substitution method) and solve:
3x-5y=-4
3x-5(x+2)=-4
3x-5x-10=-4
-2x-10=-4
-2x=6
x=-3
since we now know that x=-3, we can use it to find y by plugging in -3 for x in the top equation (you can do it in either equation, but doing it in the top equation is easier):
y=x+2
y=-3+2
y=-1
answer: (-3, -1)
<span>x+y=30.....(1) and x-y=2......(2) so(1)+(2)......x+y+x-y=30+2 so 2x=32...x=16 now apply x=16 in (1) so we get......16+y=30 so .......y=14</span>
Answer:
X=35
Step-by-step explanation:
simplify 7/9
x/45-7/9=0
simplify x/45
x - (7 • 5)/45= x - 35/45
x-35/45=0
add 35 to both sides
x=35
I tried it's hard to write it all out on here i just to give u the best sorry :)
Answer:
Step-by-step explanation: answer is B
Answer:
y=4
Step-by-step explanation:
Since the slope is constant, and the only y value for each x value is 4, then the equation is y=4.